A study on supracondylar spur (process) of humerus - a case report - M Mahima Sophia; R Kalpana (Wolters Kluwer Medknow Publications, 2014)
The supracondylar spur of humerus is one of the rare anatomic variation of distal end of humerus. The overall incidence is 0.3-2.7 % of the general population, here the authors report a case of supracondylar spur of humerus that was observed during a study of 100 humeri. The spur was found in the antero-medial aspect of the left humerus, 5.4 cm above the medial epicondyle. It was triangular in shape and measured about 0.8 cm in length and was directed medially and forwards. The spur was 6.5 cm above the tip of the trochlea and 23.6 cm inferior to the highest point of head of humerus. A knowledge of this anatomic variation is essentially important for clinicians, surgeons and anaesthetists, as this spur if associated with Struthers' ligament will lead to a compression of the median nerve and the brachial artery. A knowledge of this variation is also important for the radiologists during image interpretation.